Sepeda Onthel sebagai Identitas Komunitas SEPOK di Kota Pontianak - Armia Rizki Adinda; Hasanah Hasanah; Syarmiati Syarmiati (Universitas Tanjungpura, 2021)
The purpose of this research is to describe and analyze the background of the founding of the community, reveal and analyze the role in preserving the onthel bicycle, explain the function and meaning of the community for its members, and to find out the activities carried out. This paper intended to explain Onthel bicycle as Anthropological identity of SEPOK community. SEPOK is a community for onthel bike lovers in Pontianak City. This research used a qualitative method with data collection techniques of observation, interviews, and documentation. We used community and symbolic interaction as our analysis tools. The results showed that in preserving the onthel bicycle culture, the SEPOK community actively participate in various activities both carried out by the Province of West Kalimantan and other regions. Community members are quite heterogeneous and have various opinions in giving the meaning of the onthel bicycle as their symbol.